Development Trends in Pedagogical and Psychological Sciences: The Experience of Countries of Eastern Europe and Prospects of Uk 2018
DOI: 10.30525/978-9934-571-27-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Influence on Public Opinion and Youth Behavior

Abstract: Abstract. Main objective. The article deals with the key factors of the virality of media content in social networks and technical university students' media literacy in social networks. Methodology. We analyzed the concept of virality and generalized the reasons that affect the popularity of the information posted in social networks. The three main groups of virality factors were singled out: content (its subject and form), the audience and the specific character of a social network. We have also analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the proliferation and widespread usage of social media, social media platforms are now used as channels and tools for the expression of public opinion. The influence of social media platforms on public opinion has been highlighted in several studies [8]- [10]. The authors in [8] addressed the virality of social media content and its impact on youth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the proliferation and widespread usage of social media, social media platforms are now used as channels and tools for the expression of public opinion. The influence of social media platforms on public opinion has been highlighted in several studies [8]- [10]. The authors in [8] addressed the virality of social media content and its impact on youth.…”
mentioning
confidence: 99%
“…The influence of social media platforms on public opinion has been highlighted in several studies [8]- [10]. The authors in [8] addressed the virality of social media content and its impact on youth. The researchers in [9] found that social media is being used to further political interests, while the authors in [10] argue that social media is a powerful tool for persuasion and can be used to manipulate public opinion.…”
mentioning
confidence: 99%